2003
DOI: 10.1007/s00436-003-0968-5
|View full text |Cite
|
Sign up to set email alerts
|

Interactions related to non-host snails in the host-finding process of Euparyphium albuferensis and Echinostoma friedi (Trematoda: Echinostomatidae) miracidia

Abstract: In order to determine whether the miracidia of Euparyphium albuferensis and Echinostoma friedi are sensitive to their host snail (HS) and capable of discriminating between HS and non-host snails (NHS), or whether these NHS can interfere and thus reduce the infection rates (decoy effect), a total of three experiments were conducted with HS, NHS and snail-conditioned water (SCW). Gyraulus chinensis is the HS for E. albuferensis miracidia, while Physa acuta, Radix peregra and Lymnaea fuscus are considered NHS. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This may be attributed to different factors depending on snails and parasites and their complex relationships. For instance, in some snail-trematode systems, it has been demonstrated experimentally that some non-host snail species (resistant to infection) can act as a decoy, thus interfering and consequently reducing the rate of infection of the host species with which the habitat is shared [32]. Populations with phenotypic differences in susceptibility to infection by certain trematode species have also been described within the same species [33].…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to different factors depending on snails and parasites and their complex relationships. For instance, in some snail-trematode systems, it has been demonstrated experimentally that some non-host snail species (resistant to infection) can act as a decoy, thus interfering and consequently reducing the rate of infection of the host species with which the habitat is shared [32]. Populations with phenotypic differences in susceptibility to infection by certain trematode species have also been described within the same species [33].…”
Section: Discussionmentioning
confidence: 99%
“…Te prevalence of F. gigantica cercariae estimated at 21.60% in L. natalensis is higher than that reported by Iglesias-Piñeiro et al [10] in Spain (4.4%) and Mekonnen et al [71]. In contrast, Muñoz-Antoli et al [72] obtained higher prevalences (44.72%) in L. natalensis. Tese diferences could be explained by variation in ecosystems and mollusc-cercaria-animal relationships [73][74][75].…”
Section: Discussionmentioning
confidence: 62%
“…However, other studies of trematodes and gastropods have found that unintended snail hosts can be infected by trematode parasites (cause a dilution effect). For example, non-host snails can become infected with trematodes that typically infect the intended host species, but variation among infection rates of non-host snails suggests attractiveness or susceptibility to the parasites is not uniform among non-host snails [ 47 49 ]. Infection rates of Schistosoma mansoni in Biomphalaria glabrata snails (the intended host) were reduced when non-susceptible snails were also present [ 47 , 50 ].…”
Section: Discussionmentioning
confidence: 99%